2016
DOI: 10.3233/thc-161177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of joint angles and electromyographic activity of the lower extremities during standing with wearing standard and revised high-heeled shoes: A pilot study

Abstract: Abstract. Revised high-heeled shoes (HHSs) were designed to improve the shortcomings of standard HHSs. This study was conducted to compare revised and standard HHSs with regard to joint angles and electromyographic (EMG) activity of the lower extremities during standing. The participants were five healthy young women. Data regarding joint angles and EMG activity of the lower extremities were obtained under three conditions: barefoot, when wearing revised HHSs, and when wearing standard HHSs. Lower extremity jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…High heeled shoes also affect the electromyographic activity of lower extremities muscles. In revised high heeled shoes wearing study, they concluded that revised heeled shoes improve the EMG activity of lower limbs muscles and keep the body in normal alignment [11]. Long time wearing of high heeled shoes produces changes in the distribution of body weight on feet, more weight bearing on frontal part of foot [12].…”
Section: What Evidence and Literature Saymentioning
confidence: 99%
“…High heeled shoes also affect the electromyographic activity of lower extremities muscles. In revised high heeled shoes wearing study, they concluded that revised heeled shoes improve the EMG activity of lower limbs muscles and keep the body in normal alignment [11]. Long time wearing of high heeled shoes produces changes in the distribution of body weight on feet, more weight bearing on frontal part of foot [12].…”
Section: What Evidence and Literature Saymentioning
confidence: 99%